Identification of embolic stroke in patients with large vessel occlusion: The Chinese embolic stroke score, CHESS. (24th September 2021) - Hong, Lan; Lin, Longting; Li, Gang; Yang, Jianhong; Geng, Yu; Lou, Min; Parsons, Mark; Cheng, Xin; Dong, Qiang
Abstract: Aims: The aim of the study was to develop a simple and objective score using clinical variables and quantified perfusion measures to identify embolic stroke with large vessel occlusions. Methods: Eligible patients from five centers participating in the International Stroke Perfusion Imaging Registry were included in this study. Patients were split into a derivation cohort ( n = 213) and a validation cohort ( n = 116). A score was developed according to the coefficients of independent predictors of embolic stroke from stepwise logistic regression model in the derivation cohort. The performance of the score was validated by assessing its discrimination and calibration. Results: The independent predictors of embolic stroke made up the Chinese Embolic Stroke Score (CHESS). There were: history of atrial fibrillation (3 points), non‐hypertension history (2 points), and delay time>6 s volume/delay time>3 s volume on perfusion imaging ≥0.23 (2 points). The AUC of CHESS in the derivation cohort and validation cohort were 0.87 and 0.79, respectively. Patients with a CHESS of 0 could be identified as low‐risk of embolic stroke, with a CHESS of 2–4 could be identified as medium‐risk and with a CHESS of 5–7 could be regarded as high‐risk. The observed rate of embolic stroke of each risk group was well‐calibrated with the predicted rate. Conclusion: CHESS could reliably and independently identify embolic stroke as the cause of large vessel occlusion.